Vertical gardening undergirds household food security: evidence from Nairobi’s Kibera informal settlements - Otieno, Judith A.; Omia, Dalmas O.; Amwata, Dorothy A. (Frontiers in Sustainable Food Systems, 2025)
Rapid urbanization in Nairobi has intensified food insecurity, especially in informal settlements like Kibera, where 85% of residents face chronic hunger. Vertical gardening has emerged as a grassroots solution to these challenges, offering a localized, space-efficient method for improving household food security. The study investigates how vertical gardening contributes to the four dimensions of food security—availability, access, utilization, and stability—while also exploring embedded gender dynamics. The study employed a multi-method qualitative design, including in-depth interviews, focus group discussions, unstructured observations, and key informant interviews. These approaches were used to unpack labor regimes, household experiences, and the perceived value of vertical gardening in Kibera’s informal settlements. Vertical gardening was found to: Enhance availability through crop diversification and continuous production cycles, improve access by reducing reliance on market purchases and enabling surplus sales, support utilization via improved dietary diversity and safer food preparation and strengthen stability by buffering households against economic and climatic shocks. Households practicing vertical gardening reported greater resilience and nutritional security, with women playing a central role in garden maintenance and intra-household food distribution. Vertical gardening is not merely a survival strategy. It represents a transformative practice that fosters urban resilience, gender empowerment, and community solidarity. However, its scalability is constrained by insecure land tenure, limited water access, and inadequate institutional support. The paper calls for targeted investments in training, microfinance, and policy integration to embed vertical gardening within broader urban food system reforms.